Socialization of Bullying Dangers to Students at SDN Gentan 04 Susukan District Semarang Regency - Zuleika, Pegy; Hannuna, Alya Navi; Fa’izah, Raihanah Luthfi; Sha’idah, Zahra Az; Fitriyana, Nindi Rizki; Iqbal, Muhammad (PT FORMOSA CENDEKIA GLOBAL, 2024)
Bullying is a behavior in which a person or group uses power to harm another person. Bullying has been happening for a long time, and even today this behavior is still often encountered, especially in the school environment. Bullying is generally carried out and experienced by children. The methods used in this research are delivering material directly, methods of sharing, discussion, question and answer, and dialogue, and methods using interactive learning media. The results of outreach activities about the dangers of bullying at SDN Gentan 04 show the importance of equipping students with knowledge about bullying.